Caracterization of the physical aptitude in the integrants of the Barranquilla gold gymnnastic club (Original) (Revista científica Olimpia, 2024)
The practice of systematized and planned physical activity, being punctual in sports practice, exercise, physical education, are activities that have a very important role in the development of the health of each person, since these are intrinsically related to the different systems of the human organism, and it is essential when establishing the bases in good practices for the stability of our health and in athletes planning healthy sports careers, which is why physical fitness is evaluated to obtain a comprehensive evaluation of each individual. level of their capabilities. The objectives set for this research are to characterize the physical fitness of the gymnasts of the Gymnastics Gold Club of Barranquilla, to identify anthropometry, body composition, somatotype and to evaluate the levels of physical fitness by determining cardiorespiratory resistance, musculoskeletal fitness, flexibility and body composition through tests and physical tests, in gymnasts from the Gymnastics Gold Club of Barranquilla for the period 2019 - 2. The applied methodology has a descriptive evaluative transectional design, with an analytical empirical approach, and the type of research is qualitative. The sample used is 17 gymnasts from 7 to 14 years old. The conclusions obtained show us, by differentiating the ages, and having worked with the female population, it is denoted that the research participants at the level of cardiorespiratory resistance under the various energy systems in which it is manifested present, deficiencies, fitness musculoskeletal is remarkably developed at the level of the lower extremities and the trunk, with deficiencies in the upper extremities, in flexibility the participating gymnasts obtained high results, and at the level of body composition the common denominator of the body mass index is low weight , higher percentage of muscle mass and adipose mass and the characteristic somatotype of this population was the Ectomorphic with an approach to the Mesomorphic. It is recommended to establish an action plan with the objective of improving physical fitness levels according to the results at the level of the deficiencies found at a general and specific level, and improving the athlete's performance.
Keywords: Aptitud física, Resistencia Cardiorrespiratoria, Aptitud Musculoesquelética, Flexibilidad, Composición Corporal, Gimnasia